2015
DOI: 10.1155/2015/873954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sedative and Hypnotic Activity of Ethanolic Extract ofScoparia dulcisLinn.

Abstract: Scoparia dulcis Linn. (SD) is a perennial herb that has been well studied for its antioxidant, anti-inflammatory, antidiabetic, and hepatoprotective effects. However, scientific information on SD regarding the neuropharmacological effect is limited. This study evaluated the sedative and hypnotic effect of the ethanolic extract of whole plants of Scoparia dulcis (EESD). For this purpose, the whole plants of S. dulcis were extracted with ethanol following maceration process and tested for the presence of phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…As expected, similar types of effects accomplished by the administration with diazepam. Substantial evidence revealed that the CNS depressant such as TS bind to the gamma amino butyric acid type A (GABA A ) receptor complex and potential gamma aminobutyric acid (GABA) mediated hyperpolarization of postsynaptic neurons [25].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, similar types of effects accomplished by the administration with diazepam. Substantial evidence revealed that the CNS depressant such as TS bind to the gamma amino butyric acid type A (GABA A ) receptor complex and potential gamma aminobutyric acid (GABA) mediated hyperpolarization of postsynaptic neurons [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary phytochemical screening confirmed the presence of carbohydrates (seeds), saponins (flowers), phenols, flavonoids, sterols, triterpinoids, glycosides, terpenoids, and coumarins in the ethanolic extract of P. pashia while alkaloids were totally absent. There are several reports demonstrated glycosides and flavonoids in the extract possess sedative properties mediated through affinity with benzodiazepines site of GABAergic complex system or direct or indirect modulators of this receptor . Similarly, the presence of flavonoids, coumarins, phenolic acids, glycosides, and terpenoids in HEPP could be mainly responsible for sedative and hypnotic properties.…”
Section: Discussionmentioning
confidence: 97%
“…Thus the EPM test in this research work suggested the anxiolytic activity of methanol extract of T. recurva. Increase in head dipping behavior is the expression of anxiolytic state and decrease in the number of head dipping reflects the depressant effects in hole board test [19,21,22]. The hole board showed that the methanolic extract of T. recurva causes a dose dependent increase in the number of head dips in mice which is statistically significant (P < 0.001) as compared to control group.…”
Section: Discussionmentioning
confidence: 99%